1984
DOI: 10.1139/m84-163
|View full text |Cite
|
Sign up to set email alerts
|

Siderophore production by Proteus mirabilis

Abstract: Studies on the isolation and characterization of Proteus mirabilis siderophores provided no evidence that these bacteria synthesize catechol- or hydroxamate-type siderophores. However, gas chromatograph analysis in conjunction with mass spectroscopy revealed the presence of alpha-hydroxyisovaleric acid, a previously unknown metabolite. Additional substantiating evidence for the presence of alpha-hydroxyisovaleric acid in these bacteria was obtained from experiments involving the use of thin-layer chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…A smaller analog, a-hydroxyisovaleric acid, has been isolated earlier as a siderophore of P. mirabilis in low-iron medium (4). However, we found that the chain length is different, yielding a-hydroxyisocaproic acid as the predominant a-hydroxy acid; this may be due to differences in low-iron media and the corresponding changes of metabolic pathways for amino acid biosynthesis.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…A smaller analog, a-hydroxyisovaleric acid, has been isolated earlier as a siderophore of P. mirabilis in low-iron medium (4). However, we found that the chain length is different, yielding a-hydroxyisocaproic acid as the predominant a-hydroxy acid; this may be due to differences in low-iron media and the corresponding changes of metabolic pathways for amino acid biosynthesis.…”
Section: Discussionmentioning
confidence: 51%
“…Although a-hydroxyisovaleric acid had been identified earlier as a siderophore in Proteus mirabilis (4), its general importance for iron nutrition in these bacteria seems questionable, especially in the presence of amino acid-rich media. It is well known that the amino acid deaminase reaction is the most distinguishing feature of the tribe Proteeae (6) and is responsible for a wide variety of ox-keto acids produced from amino acids prevailing in a complex medium * Corresponding author.…”
mentioning
confidence: 99%
“…The addition of exogenous iron reduces the susceptibility of animals to the development of P. mirabilis pyelonephritis (131). While most enterobacteria produce phenolate (enterobactin)-and/or hydroxamine (aerobactin)-type siderophores during iron-limiting conditions (42,45,296), none of these traditional siderophores have been demonstrated to be produced in Proteus, Providencia, or Morganella species (92,296,323). It has been proposed that these bacterial genera utilize ␣-keto acids derived from the deamination of amino acid by amino acid deaminase to bind iron and act as potential siderophores (85).…”
Section: Damage To the Host And Acquisition Of Nutrientsmentioning
confidence: 99%
“…tein has been cloned from the latter two bacteria (64a, 67a). The effects of iron stress have been studied in many gramnegative bacteria, including Escherichia (12,14,36,48,53), Haemophilus (49,50), Klebsiella (33,42), Neisseria (4,58,73), Pasteurella (16,31,55,66), Pseudomonas (60), Proteus (18), Salmonella (17,20,75), Serratia (46), Shigella (57), Vibrio (2,15,37,69), and Yersinia (8,9,61) spp. These bacteria synthesize numerous iron-regulated membrane proteins (IRMP) whose biochemical functions are for the most part uncharacterized.…”
mentioning
confidence: 99%